Akuntabilitas Pengelolaan Dana Zakat Berbasis Teknologi Informasi Pada Organisasi Pengelola Zakat (OPZ) - Suginam Suginam (Forum Kerjasama Pendidikan Tinggi, 2020)
The purpose of this study is to see the level of optimization of zakat fund collection in the presence of digital-based zakat. The use of information technology to support better zakat management is urgently needed. Because, with the use of Information Technology, zakat management that is trustworthy, professional, transparent, accountable and takes into account sharia compliance can be realized. A better information system is expected to increase the trust (trust) of the public in Zakat Management Organizations. The technological era requires zakat management organizations (OPZ) to transform themselves into the digital realm. Therefore, one aspect of realizing the zakat awakening period is to optimize zakat management by prioritizing digital-based information technology aspects. This research is a qualitative descriptive study using a literature study approach, which is taken from various scientific articles related to scientific topics, books, news and journals. The results of this study will be able to provide solutions to problems that occur related to the inadequate use of information technology as an information medium that is able to provide information and literacy to the public, especially to muzakki.